THE CHANGING CONCEPT OF RURAL COMMUNITY AND ITS IMPORTANCE IN CONNECTION WITH THE TRANSFER OF AGRICULTURAL LAND - Szilágyi, János Ede (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Primarily focusing on the European Union (EU) law and the national law of the Member States of the EU, this paper presents the changing legal concept of rural communities and/or agricultural communities (hereinafter together referred to as rural communities). Since the EU’s concept of rural communities is significantly based on the definition provided by the Council of Europe, hence, the paper also assesses the background of the rural communities’ concept connected to the Council of Europe, namely, the European Charter for Rural Areas and scientific reports connected to the Charter. The legal definition of rural communities is elementary for Hungary – among others – since the conservation of rural communities was a determining reason at the time of the adoption of the new Hungarian land law. According to the jurisdictions of the Court of Justice of the European Union, certain aspects of the conservation of rural communities shall serve as a legal public interest objective for national measures concerning land transactions. Therefore, this situation raises the question: what does the term ‘rural community’ mean.